2001
DOI: 10.1002/mma.250
|View full text |Cite
|
Sign up to set email alerts
|

Existence and uniform decay for a non‐linear viscoelastic equation with strong damping

Abstract: SUMMARYThis paper is concerned with the non-linear viscoelastic equationWe prove global existence of weak solutions. Furthermore, uniform decay rates of the energy are obtained assuming a strong damping ut acting in the domain and provided the relaxation function decays exponentially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
151
0
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(168 citation statements)
references
References 7 publications
2
151
0
15
Order By: Relevance
“…Now we state a local existence theorem for solutions of the system (1.1) that can be established by combining the arguments in [1,6,27].…”
Section: Lemma 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Now we state a local existence theorem for solutions of the system (1.1) that can be established by combining the arguments in [1,6,27].…”
Section: Lemma 25mentioning
confidence: 99%
“…The following initial boundary value problem: 6) has been investigated by many people. When ρ = 0 and there are no dispersion terms, in the absence of strong damping ( γ i = 0), the system has been investigated by several authors and results concerning existence, decay, and blow-up were obtained [1,2,15,22,25,26,28,29,32,36].…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, la dinámica de los materiales viscoelásticos son de gran importancia e interés ya que tienen amplias aplicaciones en la física y la ingeniería. Más información al respecto, ver [3,6,21].…”
Section: Introductionunclassified
“…que ha sido estudiado por muchos autores, y sus resultados relativos a la existencia, comportamiento asintótico y explosión de soluciones han sido establecidos recientemente, ver por ejemplo [3,7,10,11,12,16]. Aquí, entenderemos que −∆u , t 0 g (t − s) ∆u (s) ds, − ∆u y f (u) son los términos de dispersión, disipativo de viscoelasticidad, disipativo de viscosidad y fuente, respectivamente.…”
Section: Introductionunclassified
“…For the same problem (1.5), in [13], Song and Zhong showed that there were solutions of (1.5) with positive initial energy that blew up in finite time. For more related works, we refer the reader to [14]- [18].…”
Section: Introductionmentioning
confidence: 99%